Cultura de café (Coffea arábica L.) com princípios agroecológicos como opção para a agricultura familiar na região de Penápolis/SP - Zago, Sebastião (Universidade Federal de São Carlos, 2008)
The county of Penápolis and region, located into the northwest of São Paulo state, was deforested by coffee growing and they became strong producers in the beginning of the past century, influencing on the plan of the railroads on diffusion of the immigrants. But, due to economic factors, climatic and politicians, this culture has been replaced by others activities agriculture, developed for the big properties, such as the sugar cane and the meadow, overwhelming so, the familiar agriculture that if turned out inoperable on conventional molds of production, causing the removal of the little farmer to the city in search of others fountains of income. The purpose of this work was the following-up the formation and handling of a experimental farming of coffee on agroecologic molds and the definition of the indicators of sustainability for the assessment and comparison of results with others cultivations of conventional principles, organic and a fragment of natural forest, for parameters for analysis, assessment and implementation of this system of cultivation on region. In this work, it concluded that the coffee on agroecologics molds promoted sensitive physical-chemical and biological transformations in the system, indicating that, the use of alternative techniques of production combined with coffee cultivation tradition and the farmer s capacity it s possible to make the coffee culture as an alternative to family farming in the region.
Coffee culture (Coffea arabica L.) with agroecological principles as option for family agriculture in the region of Penápolis / SP
Keywords: Colonização; Café - cultivo; Agroecologia; Agricultura familiar; Sustentabilidade; Cafeicultura; Colonization; Coffee growing; Agroecologic; Family agriculture; Sustainability; CIENCIAS AGRARIAS